Reassessing Judicial Standards of Proof for Structured, Systematic, and Massive Electoral Violations in Indonesian Regional Head Election Disputes - Sayuti Sayuti; Miftahul Choiri; Mesut Idriz (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
Electoral disputes are a fundamental mechanism for safeguarding democratic legitimacy and ensuring the integrity of electoral processes. In Indonesia, the Constitutional Court holds a pivotal role in adjudicating disputes over regional head election (pemilihan kepala daerah /Pilkada) results. Nevertheless, the judicial standard for proving structured, systematic, and massive (TSM) violations remains deeply contested, as many petitions are dismissed at the preliminary stage due to procedural barriers such as vote-margin thresholds and strict legal standing requirements. This procedural formalism restricts substantive judicial scrutiny of systemic electoral misconduct and weakens electoral integrity, electoral justice, popular sovereignty, and democratic legitimacy. This study aims to critically reassess the existing judicial standards for proving TSM violations and to reconstruct a more balanced adjudicative framework between legal certainty and substantive electoral justice. Employing normative legal research through statutory, conceptual, and case approaches, this study examines Constitutional Court decisions concerning regional election disputes. The findings reveal that the prevailing adjudicative model remains excessively outcome-oriented, prioritizing quantitative vote margins over qualitative assessment of electoral integrity. The novelty of this study lies in the formulation of a three-layer judicial test—institutional involvement, systematic design of violations, and electoral impact—as a reconstructed evidentiary framework for TSM adjudication. Theoretically, this model contributes to the literature on electoral justice by shifting judicial review from a result-based paradigm toward a process-integrity approach, thereby strengthening democratic legitimacy within Indonesia’s constitutional democracy.